2015
DOI: 10.5714/cl.2015.16.1.034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface treatment of graphene nanoplatelets for improvement of thermal and electrical properties of epoxy composites

Abstract: In this study, in order to improve the thermal and electrical properties of epoxy/graphene nanoplatelets (GNPs), surface modifications of GNPs are conducted using silane coupling agents. Three silane coupling agents, i.e. 2-(3,4-epoxycyclohexyl)-ethyltrimethoxysilane (ETMOS), 3-glycidoxypropyltriethoxysilane (GPTS), and 3-glycidoxypropyltrimethoxysilane (GPTMS), were used. Among theses, GPTMS exhibits the best modification performance for fabricating GNP-incorporated epoxy composites. The effect of the silaniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Kim et al . 23 found that surface-treated GNP reduce interfacial resistance between nanoparticles and the polymer matrix, improving thermal conductivity. Another option is to align nanofillers by an electric field.…”
Section: Introductionmentioning
confidence: 98%
“…Kim et al . 23 found that surface-treated GNP reduce interfacial resistance between nanoparticles and the polymer matrix, improving thermal conductivity. Another option is to align nanofillers by an electric field.…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, Figure 6b AGO-100, Figure 6c GGO-100 and Figure 6d AGO-150 and Figure 6e GGO-150 samples exhibit rough surface with wrinkle morphology and the inserted magnified image on all the four samples shows several thin sheets with puffy structures [22], which signify the present of silane moieties that act as a spacer between the GO sheets and hence preventing restacking [24,25]. The distinction in morphology observed between GO and the functionalized-GO results from covalent bonding and condensation reactions between silanes molecules and GO sheets which subsequently hinders agglomeration [26].…”
Section: Resultsmentioning
confidence: 99%
“…By utilizing layered reinforcements with a large aspect ratio, such as graphite flake, which can be exfoliated and dispersed in a polymer matrix as nanoplatelets, polymer nanocomposites have exhibited improved mechanical, thermal and barrier properties, depending upon the type of nanoplatelets [73][74][75].…”
Section: Improvement In Adhesion Of Carbon Fiber/ Bmi Composites Usinmentioning
confidence: 99%